Associations between plasma beta amyloid and cognitive decline: A systematic review and meta-analysis - Cynthia, Cynthia; Nugraha, Jusak; Hamdan, Muhammad; Dharma, Rahajuningsih; Lumempouw, Silvia F. (Narra Sains Indonesia, 2025)
Alzheimer’s disease is a leading neurodegenerative disorder characterized by progressive cognitive decline. Early prediction is crucial for enabling timely interventions. Plasma amyloid β-peptides (Aβ), particularly the Aβ-42/Aβ-40 ratio, have been proposed as potential non-invasive biomarkers for cognitive decline and Alzheimer’s disease risk. However, conflicting findings and methodological variability have hindered consensus regarding their clinical utility. The aim of this study was to evaluate whether the plasma Aβ levels predict dementia, Alzheimer’s disease, and cognitive decline. Studies were eligible for inclusion if they measured at least one plasma Aβ species (Aβ-40, Aβ-42, or the Aβ-42/Aβ-40 ratio) and reported outcomes related to dementia, Alzheimer’s disease, or cognitive change. Only human studies published in peer-reviewed journals were included. A comprehensive search of six databases (PubMed, PMC, SSRN, Scopus, BioRxiv, and MedRxiv) was conducted up to December 1, 2024. Risk of bias was assessed using the ROBINS-E tool, and pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using a random-effects meta-analysis. A total of 25 studies were included in the systematic review, with four contributing to the meta-analysis. Lower plasma Aβ-42/Aβ-40 ratio was not significantly associated with Alzheimer’s disease risk (pooled HR=0.8; 95%CI: 0.62–1.04), and substantial heterogeneity was observed (I²=70%, p=0.02). Individual studies varied in their findings: while some reported that lower Aβ-42/Aβ-40 ratio predicted increased Alzheimer’s disease risk, others found no association or even opposing trends. Methodological heterogeneity—including differences in sample handling, measurement techniques, and study designs—likely contributed to these inconsistencies. Overall, this review suggests that plasma Aβ-42/Aβ-40 ratio is not reliable predictors for the onset of Alzheimer’s disease or dementia. However, the substantial heterogeneity observed underscores the need for further research to clarify the potential of plasma Aβ as a preclinical biomarker.